(5x^2-21x-20)/(5x^2-16x-16)
((x-5)(5x+4))/((x-4)(5x+4))
(x-5)/(x-4)
x² - 3 x - 54 = x² + 6 x - 9 x - 54 = x ( x + 6 ) - 9 ( x + 6 ) = ( x + 6 ) ( x - 9 )
x² - 18 x + 81 = ( x - 9 )²
x² + 12 x + 36 = ( x + 6 )²
... = ( x + 6 ) · ( x - 9 ) / ( x - 9 )² * ( x + 6 )² / ( x + 6 ) = ( after cancellation )
= ( x + 6 )² / ( x - 9 )
After solving the given problem, I’ve been able to get 3(x-2) / 2(x-3) as the simplified form of the given equation. I am hoping that this answer has satisfied your query and it will be able to help you, and if you would like, feel free to ask another question.
If I understand clearly, the expression is
(18st^4/52s^3t)(16s^3/9s^2t)
To simply the expression, we simply have to multiply the constants and reduce the product to the lowest terms and apply the laws on exponents to simplify the variables. So, the answer would be:
8t^2/13s
(40v^2)/(35v^4) / (20v^3)/(5v)
(8)/(7v^2) / (4v^2/1)
(8)/(7v^2) * (1 / 4v^2)
2/(7v^4)
Answer:
8x-1
Step-by-step explanation:
add up all the x's which will be 8x
then do the regular numbers which is -2+1 is -1
therfore it is 8x-1
Add total hours worked (14+20=34) and multiply by hourly pay rate($9)
34
x9
306
<u>4</u> - <u> x + 2</u> = <u>2 + x</u>
x x x
Answer:
I don’t know
Step-by-step explanation: